If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(2y-2)+2y=4(y+4)
We move all terms to the left:
-6(2y-2)+2y-(4(y+4))=0
We add all the numbers together, and all the variables
2y-6(2y-2)-(4(y+4))=0
We multiply parentheses
2y-12y-(4(y+4))+12=0
We calculate terms in parentheses: -(4(y+4)), so:We add all the numbers together, and all the variables
4(y+4)
We multiply parentheses
4y+16
Back to the equation:
-(4y+16)
-10y-(4y+16)+12=0
We get rid of parentheses
-10y-4y-16+12=0
We add all the numbers together, and all the variables
-14y-4=0
We move all terms containing y to the left, all other terms to the right
-14y=4
y=4/-14
y=-2/7
| -6(v+4)=-36 | | 137=108+x | | 90=9x+3 | | 37=-3-2a | | -5=p–9/4 | | 4(v+1)-v=3(v+1)+3 | | x+7=-3x-29 | | 6y-7/4=-3/4y-1/3 | | 4(u-1)-4=-2(-6u+7)-4u | | 3(2x-4)+12x=30 | | 2(u+1)+8=9(2u+4) | | 42=-6r-18 | | x+23=5x-1 | | 42=-6r–18 | | -2(x-4)=4x-14 | | 4x-3-5x+11=15x+16 | | y=−4 | | 4w-8=-56 | | 3(x-2)=5x=9-4(x=3) | | x*6=186 | | -4w–8=-56 | | 1/3*2x+9)=2/3x | | 4x-18=-3x-8 | | -2(x-4)=9x-14 | | -10=-4v+9v | | -4(z-6)=8 | | -4(z–6)=8 | | -4(-6x+2)-2x=4(x-3)-5 | | (3^x+1)=28 | | 9x+17=-17+9x | | 2(2x+1)=10x | | 2s+6=5 |